Structural evaluation of dynamic and semi-static displacements of the Juarez Bridge using GPS technology. (November 2017) - Vazquez B., G. Esteban; Gaxiola-Camacho, J. Ramon; Bennett, Rick; Guzman-Acevedo, G. Michel; Gaxiola-Camacho, Ivan E.
Highlights: Real-time performance evaluation of bridges. Health assessment of civil infrastructure using GPS. Serviceability design limit states of bridges. Structural reliability evaluation of bridges in terms of probability of failure. Abstract: Global Positioning System (GPS) naturally produces position estimates representing a considerable advantage in comparison with others assessment instruments such as accelerometers, where double integration is required. Several investigations have demonstrated that GPS is an accurate and efficient tool for the evaluation of civil infrastructure. Therefore, an alternative bridge structural evaluation focused on in-service conditions of the Juarez Bridge located in Culiacan, Mexico by using GPS is addressed in this research. The Juarez Bridge connects two important zones of the city, it is a reinforced concrete structure constructed approximately 45 years ago, and it has a length closely to 200 m. The assessment process consisted in collecting continuous GPS data during one consecutive hour at three different periods of the day (rush hours) from Monday to Sunday under critical traffic loading. Since the response of a structure subjected to loads may result in different types of displacements, GPS time series were used for the proper calculation of dynamic and semi-static displacement at the center deck of the Juarez Bridge. However, GPS displacements obtained in terms of coordinates may not accurately reveal the behavior of the bridge without considering prior filtering of the data. Hence, two post-processing reliable filtering techniques: the moving average and Chebyshev filter were applied to improve the time series. It was observed that the vertical displacements were critical during the evaluation. Hence, vertical semi-static displacements were compared with respect to the AASHTO (American Association of State Highway and Transportation Officials) deflection limits, and probability of failure was properly calculated.